Integrated Disease Management Wilt of Lentil Caused by Fusarium oxysporum f. sp. Lentis - Dubey, Khushboo; Singh, S.K. (International Journal of Scientific Research in Biological Sciences, 2021)
Effect of chemical, bio-agents and Rhizobium was tested alone and in combination to see their individual as well as combined effect on wilt disease management in pot under net house conditions. Eighteen treatments were under taken in this study, among them highest per cent disease control (70.89%) was recorded with Rhizobium (ST)+ Carbendazim.(ST)+ Pseudomonas sp.(SoilT) followed by Rhizobium(ST)+Carbendazim.(ST)+ Bacillus subtilis (SoilT) (67.05), Rhizobium (ST)+Carbendazim. (ST)+T.h. (64.64%), Rhizobium(ST) + soilT T.harzianum (63.36%), Rhizobium(ST) + Carbendazim. (ST) (59.47%), Rhizobium(ST) + Pseudomonas fluorescens (SoilT) (58.94%), Rhizobium(ST)+Bacillus subtilis (SoilT) (57.12%), Rhizobium(ST) + T.harzianum(SoilT) (56.66%), Rhizobium(ST) + T.harzianum(ST) (56.41%), Carbendazim.(ST) (52.48%), Pseudomonas fluorescens (SoilT) (49.92%), Bacillus subtilis (SoilT)(46.24%), T. harzianum (SoilT) (43.52%), Pseudomonas fluorescens (ST) (42.08%), Bacillus subtilis (ST) (39.04%), T. harzianum(ST) (35.89%) and Rhizobium(ST) (17.58%) as compared to untreated pots during 2016-17.